AI in News Radio: Navigating Technology while Preserving Human Connection and Journalistic Values (A Case Study of Three News Radio Stations in Jakarta, Indonesia) - Fadilah, Efi; Muslikhin, Muslikhin; Andayani, Fitri; Aristi, Nindi (Jurnal Sosioteknologi, 2025)
Since the public's adoption of ChatGPT in 2022, concerns have arisen about the possibility of AI will replace human roles across various industries, including radio broadcasting. While many radio professionals argue that AI will not diminish the importance of human involvement, some stations are already incorporating AI technologies. This study examines AI adoption in three news radio stations in Jakarta, focusing on its usage, guidelines, and future implementation plans. Utilizing a qualitative case study method, data were gathered through interviews with editors, observations, and literature review. The results show that initially, AI was not considered essential in news radio due to its simple production; however, its development is closely monitored. While AI improves efficiency, concerns about over-reliance on technology impacting human relationships persist. Radio managers must balance technological progress with human connections and uphold journalistic standards to maintain listener trust. Stations differ in their AI use—some utilize it for specific tasks, while others integrate it into operations and customize their content. There are no formal internal guidelines for AI in journalism, highlighting the importance of the guidelines from the Indonesian press council. AI serves in editorial processes, but the human role remains central in news judgment. The broadcaster-listener relationship remains vital; however, it is important to consider the shifting patterns of media consumption.